Molecular and Electronic Structure of the Cluster [Au8(PPh3)8](NO3)2. Issue 7 (25th January 2016) - Gutrath, Benjamin S.; Schiefer, Frank; Homberger, Melanie; Englert, Ulli; Şerb, Mihaela‐D.; Bettray, Wolfgang; Beljakov, Igor; Meded, Velimir; Wenzel, Wolfgang; Simon, Ulrich
Abstract: We present a detailed structural discussion of [Au8 (PPh3 )8 ](NO3 )2, crystallized as a CH2 Cl2 solvate. Its structure is compared with closely related triphenylphosphine‐stabilized gold clusters. Characterization by optical extinction spectroscopy, luminescence spectroscopy, voltammetry and DFT calculations was performed to determine the electronic HOMO–LUMO gap. Comparison of its characteristic energies with those of structurally related clusters revealed that the evolution of the HOMO–LUMO gap does not follow a simple scaling law but depends on specific structural features. Abstract : A detailed structural characterization together with an experimental (optical extinction spectroscopy, luminescence spectroscopy, voltammetry) and DFT‐based analysis of the electronic structure of the triphenylphosphine‐stabilized cluster [Au8 (PPh3 )8 ](NO3 )2 gives an insight into structure–property relationships.